Implementasi Nilai-Nilai Moderasi Agama dalam Interaksi Sosial Budaya Siswa SMP Kecamatan Sukapura Kabupaten Probolinggo - Winda Septiana; Babul Bahrudin; Roby Firmandil Diharjo (Universitas Muhammadiyah Mataram, 2025)
Abstract: Indonesia is a country with the largest Muslim population in the world, which also possesses a very rich diversity of religions, cultures, and ethnicities. This study aims to examine the implementation of religious moderation values in the socio-cultural interactions of students at SMPN 1 Sukapura, Sukapura District, Probolinggo Regency. The research focuses on four main indicators of religious moderation, namely national commitment, tolerance, anti-violence, and accommodative attitude towards local culture. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students from diverse religious and cultural backgrounds. Data analysis uses the Miles and Huberman model, which includes data collection, condensation, presentation, and conclusion drawing. The findings reveal that national commitment is reflected in students’ active participation in national activities; tolerance is manifested through harmonious interfaith interactions; anti-violence is internalized through a culture of peaceful conflict resolution; while accommodative values are evident in students’ involvement in Tengger cultural traditions. These results indicate that the school plays an essential role as an agent of socialization for moderation values, where symbolic interactions among educational actors shape students’ identity as moderate individuals. The study concludes that the implementation of religious moderation values at SMPN 1 Sukapura is comprehensive, integrated into the curriculum, extracurricular activities, and school culture, thereby fostering harmony within a multicultural educational environment.Abstrak: Indonesia merupakan negara dengan populasi Muslim terbesar di dunia, yang juga memiliki keberagaman agama, budaya, dan etnis yang sangat kaya. Penelitian ini bertujuan mengkaji implementasi nilai-nilai moderasi beragama dalam interaksi sosial budaya siswa di SMPN 1 Sukapura, Kecamatan Sukapura, Kabupaten Probolinggo. Fokus penelitian diarahkan pada empat indikator utama moderasi beragama, yakni komitmen kebangsaan, toleransi, anti-kekerasan, dan akomodatif terhadap budaya lokal. Pendekatan yang digunakan adalah kualitatif dengan jenis studi kasus. Data diperoleh melalui wawancara, observasi, dan dokumentasi terhadap kepala sekolah, guru, serta siswa yang memiliki latar belakang agama dan budaya berbeda. Analisis data menggunakan model Miles dan Huberman yang meliputi pengumpulan data, kondensasi, penyajian, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa nilai komitmen kebangsaan tercermin dalam partisipasi aktif siswa pada kegiatan kebangsaan; nilai toleransi diwujudkan melalui interaksi harmonis lintas agama; nilai anti-kekerasan terinternalisasi melalui budaya penyelesaian konflik secara damai; sedangkan nilai akomodatif tampak pada keterlibatan siswa dalam tradisi masyarakat Tengger. Temuan ini mengindikasikan bahwa sekolah berperan penting sebagai agen sosialisasi nilai moderasi, di mana interaksi simbolik antaraktor pendidikan membentuk identitas siswa sebagai pribadi moderat. Penelitian ini menyimpulkan bahwa implementasi nilai-nilai moderasi beragama di SMPN 1 Sukapura berlangsung menyeluruh, baik melalui kurikulum, kegiatan ekstrakurikuler, maupun budaya sekolah, sehingga mampu menjaga harmoni dalam lingkungan pendidikan multikultural.